A completely integrable case in the complex Lorenz equations - Flessas, G. P.; Leach, P. G.L. (HNPS Advances in Nuclear Physics, 2020)
By application of the Lie theory of extended groups and for the parameter values σ=1/2, b=1, r1= e^2/2, r2=e/2, e arbitrary we prove that the system of the complex Lorenz equations is algebraically completely integrable. The respective general exact solution i expressed by means of Jacobian elliptic functions